Use of antipsychotic blood levels in clinician decision making: A cross-over study using clinical vignettes of patients with schizophrenia. (September 2018) - Savitz, Adam; Melkote, Rama; Riley, Ralph; Pobre, Maria A; McQuarrie, Kelly; Williamson, David; Banderas, Benjamin
Highlights: CASP was developed to capture clinical decision making in patients with schizophrenia. Providing ABLs under descriptive conditions were used to evaluate treatment decisions. Clinicians responded they were more confident in their decision making using ABLs. Abstract: The cause of treatment failure of antipsychotic medications is often difficult to determine in patients with schizophrenia. Evaluation of antipsychotic blood levels (ABLs) may aid clinicians in determining the cause of antipsychotic failure. The Clinical Assessment of the Schizophrenia Patient (CASP) was developed to evaluate clinical decision making during outpatient visits. The CASP assesses changes in medications, psychosocial treatments, and acute interventions along with factors influencing clinical decision making. Nine vignettes representative of clinical situations in patients with schizophrenia were created in two versions (one with ABLs, one without ABLs). The CASP was used to evaluate clinical decisions using the vignettes. Thirty-four clinicians participated in the study. In 8 out of 9 vignettes, most clinicians (at least 89.7%) made a different clinical decision with ABLs compared to without ABLs. In assessing the usefulness of ABLs, a majority (60.7%–85.7%, depending on the vignette) of clinicians responded that ABLs changed their clinical decision for 8 vignettes. Most clinicians (79%–93%) responded that they were more confident in their decisions with ABL information. This study demonstrated that ABLs have the potential to influence clinical decision making in the treatment of patients with schizophrenia.